Human Rights Violations in the Development of the Super Priority Tourism Destination Labuan Bajo - Pahlevi, Muhammad Reza (Departemen Sosiologi Universitas Gadjah Mada, 2024)
Globalization offers various features such as the presence of Global Travel which continues to overgrow. However, Indonesia is still ranked at the bottom of tourist visits that compared to neighboring countries, therefore the Government plans to develop Destinasi Super Prioritas (DSP) or Super Priority Destinations. Labuan Bajo is the only one of the 5 areas that will be created. So, the author is interested in seeing the impact of the development of the DSP area in Labuan Bajo on fulfilling the human rights of the local community. In order to provide the recommendations for solutions to these issues the research method is descriptive qualitative by using the secondary data. To answer the problem formulation, the author uses the thinking framework of Peter M Burns on Tourism and Politics Global Frameworks and Local Realities, and Alyson Brisk on the Introduction: Transnational Threats and Opportunities. The results show that in the process of the Labuan Bajo DSP's social presence, various kinds of human rights violations occurred, starting from the loss of the right to work and obtain food security, the right to private property, the right to do the same before the law, the right to shelter and the environment. These conditions occur because there is a friendship relationship between the Government and Investors through regulatory support to State apparatus so that local communities is becoming the victims of this asymmetric relationship. This condition received resistance from the civil society alliances by using networks, solidarity, and social media.